2017
DOI: 10.1111/plb.12641
|View full text |Cite
|
Sign up to set email alerts
|

Pollination and reproductive system of synchronopatric species of Cactaceae (Cactoideae) subject to interspecific flow of pollen: an example of ecological adaptation in the Brazilian Chaco

Abstract: Three synchronopatric Cactaceae species, Echinopsis rhodotricha, Harrisia balansae and Praecereus saxicola, have mostly nocturnal anthesis and similar flowers, characteristics that motivated us to perform a comparative study of reproductive ecology. Reproductive phenology was sampled monthly from December 2014 to November 2015. We describe floral biology, breeding system via pollination treatments and evaluate floral visitors from focal and filming observations. Pollen grains found on moth proboscis were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 80 publications
0
14
1
1
Order By: Relevance
“…We conducted the study at two sites in Porto Murtinho, Mato Grosso do Sul, Brazil: Anahí Farm (AF) (21°41'13.05" S, 57°44'08.02" W) and Retiro Conceição Farm (RCF) (21°40' 57.38" S, 57°46'44.46" W) from April 2015 to March 2016 and in October–December 2016 only at RCF. For a complete description of the vegetation type in the study region, see Ferreira et al ().…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted the study at two sites in Porto Murtinho, Mato Grosso do Sul, Brazil: Anahí Farm (AF) (21°41'13.05" S, 57°44'08.02" W) and Retiro Conceição Farm (RCF) (21°40' 57.38" S, 57°46'44.46" W) from April 2015 to March 2016 and in October–December 2016 only at RCF. For a complete description of the vegetation type in the study region, see Ferreira et al ().…”
Section: Methodsmentioning
confidence: 99%
“…We also checked other floral attributes, such as anthesis time, floral longevity, number of open flowers by day, stigmatic receptivity (based on turgor aspect, either ‘moist’ or ‘glossy’) and pollen viability in five flowers (with carmine acetic) (Ferreira et al ).…”
Section: Methodsmentioning
confidence: 99%
“…In the Brazilian Chaco, a high frequency of visits comes from thieves and other non-pollinators (e.g., florivores and robbers) (Souza et al 2017), especially Cactaceae (Gomes et al 2016;Ferreira et al 2018). Most Cactaceae species in the Brazilian Chaco have long tubular flowers and high nectar production (Gomes & Araujo 2015;VGN Gomes et al 2019), which are traits related to nectar robbing (Maruyama et al 2015;Rojas-Nossa et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These gradients generally covary with climatic factors, which in turn may impact the pollination process even at small geographical scales (Kay & Sargent, 2009;Chalcoff, Aizen & Ezcurra, 2012). Little attention has been paid to the study of pollination of nearby species that co-occur sympatrically in specific geographic areas sharing the same bioclimatic variables and pollinator biota (but see Marques et al, 2007;Ferreira et al, 2018). In general, noticeable floral divergence (e.g., phenology and morphology among others) may contribute to differences in pollinator guild among evolutionarily closely related taxa that co-occur, and ultimately mediates a reduction in pollination niche overlap (Cuautle & Thompson, 2010;Grossenbacher & Whittall, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…On smaller scales, studies have shown geographical co-variation between pollinator assemblages and floral morphology (Schlumpberger et al, 2009;Walter, 2010). Unfortunately, most cacti pollination studies have mainly focused on a single plant species (Mandujano et al, 2010;Larrea-Alcázar & López, 2011;Eggli & Giorgetta, 2015), meanwhile the pollination processes of sympatric cacti have received less attention (but see Fleming, Tuttle & Horner 1996;Eggli & Giorgetta, 2017;Ferreira et al 2018). Increasing knowledge of pollination in sympatric cacti species allows us to identify potential pollen limitation and reproductive isolation barriers as well as mechanisms of seed production, which are relevant issues to identify demographic bottlenecks of taxa, especially in those with high extinction risk.…”
Section: Introductionmentioning
confidence: 99%